Older child adoption: A study of the affiliation process - Carolina Lemos da Silva; Silvia Pereira da Cruz Benetti (Estudos de Psicologia (Campinas))
This study's aim was to present a case study on the adoption of two older siblings and interpret how paternal filiation was constructed in this process. Data was collected through interviews held in 14 meetings over the course of six months. Data were also obtained from personal diaries completed by the participants. The material was analyzed based on the psychodynamic approach to identify specific aspects of parenthood and filiation, as well as utilizing the stages of the family living together. Listening to the family at times of greater ambivalence at different stages helped the adoption process and the children's filiation. The conclusion is that forming a family in adopting older children should not be associated with greater difficulties in filiation, as long as that appropriate support is provided to meet both the parents' and the children's needs concerning the process.